PSYCHIATRIC NOSOLOGY IN THE LIGHT OF EVOLUTION: Psychiatry and evolution - Nešić, Milica (Engrami, 2023)
Evolution is under-studied in medicine, psychology, and neuroscience. For this reason, these disciplines are deprived of the important insights about the human brain. Our species has had a long and complex history which has shaped the current form and function of out mental apparatus. Indeed, many of our brain s features make sense only when compared to other animal species, especially those with which we share ancestry. This paper has two goals. The first one is to lay out the basic principles of evolution which have contributed to our species vulnerability to psychiatric disorders. The second goal is to consider the validity of current psychological concepts and classifications of psychiatric disorders in light of the most recent findings from evolutionary biology and neuroscience.